Use of FMF algorithm for prediction of preeclampsia in high risk pregnancies: a single center longitudinal study - Petar Cabunac; Nataša Karadžov Orlić; Daniela Ardalić; Barbara Damnjanović Pažin; Srđan Stanimirović; Gorica Banjac; Aleksandra Stefanović; Vesna Spasojević- Kalimanovska; Amira Egić; Nina Rajović; Nataša Milić; Željko Miković (Taylor & Francis Group, 2021)
OBJECTIVE: This study aimed to assess the accuracy of The Fetal Medicine Foundation (FMF) screening algorithm for the prediction of preeclampsia. METHODS: Out of 138 women with high-risk pregnancies prospectively followed, 30 developed preeclampsia. The clinical examination and biochemical measurements were performed at first, second, early and late third trimester. RESULTS: A lower PAPP-A levels were found in the first trimester, while sFlt/PlGF was increased in the second and early third trimester in preeclampsia (p>0.05). FMF algorithm presented higher specificity (>70%), but had a drawback of lower sensitivity (35-77%). CONCLUSION: FMF algorithm had modest performance in the prediction of preeclampsia for high-risk pregnancies.